Paper Dolls : Female Stereotypes in Anglo-American Music from the 1950s and the 1960s - Miguel Alarcão, (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
This article puts up for a brief cultural comment some videoclips of Anglo-American songs from the 1950s and the 1960s, which, while displaying the visual centrality of women and the beauty of the female body, also (re)produce stereotyped gender images, as well as overt or implicit macho assumptions and prejudices.